Relationship between positive peritoneal fluid cytology and the type of the malignancy in patients with malignancy related ascites - Turanli, Sevim; Oksuzoglu, Aysegul (Annals of Medical Research, 2021)
Aim: Malignancy related ascites may be due to abdominal origin, extraabdominal origin and primary peritoneal malignancy. The relationship between positive peritoneal fluid cytology and the type of the malignancy and the burden of the tumor in the abdomen was investigated.Materials and Methods: One-hundred eighty-nine consecutive patients with malignancy who were examined for ascites fluid cytology were retrospectively identified in the last two years. Age, gender, primary tumor site, radiologic imaging and pathology results of the patients were recorded. According to the abdominal imaging at the time of the paracentesis procedure, the extensiveness of disease in the abdomen was classified as only ascites, ascites with peritoneal carcinomatosis, ascites with liver involvement (primary tumor or metastases) and ascites with peritoneal carcinomatosis with liver involvement. Results: Out of 189 patients, 119 patients (63.0%) were female. The primary tumor site was ovary in 49 patients, stomach in 38 patients, pancreatobiliary system in 37 patients, breast in 16 patients, colorectal in 14 patients, uterine in 13 patients, kidney or bladder in 6 patients, liver in 6 patients, lymphoma in 4 patients, malignant mesothelioma in 3 patients, lung in 2 patients and skin in one patient. Peritoneal fluid cytology revealed malignant cells in 102 patients (54.0%), while 87 patients (46.0%) had benign results. There was a relationship between primary tumor site and malignant cell detection in the fluid (p= 0.001). The detection of malignant cells was correlated with abdominal extensiveness of disease as well (p = 0.01). In multivariate analysis, only primary tumor site [(p = 0.001), risk ratio: 2.28, 95% confidence interval: 1.83-2.73] was the independent factor affecting cytologic positivity.Conclusion: Considering primary tumor site and the extensiveness of disease in the abdomen, primary tumor site was the most important factor affecting peritoneal fluid positivity.
Keywords: Cytology; malignancy; peritoneal carcinomatosis; peritoneal fluid